1979
DOI: 10.1901/jaba.1979.12-355
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sequential Pictorial Cues, Self‐recording, and Praise on the Job Task Sequencing of Retarded Adults

Abstract: The present study investigated the effects of a self-recording procedure using sequentially organized picture cues on independent task changes of four mentally retarded adults. Independent task changes were identified as the beginning of new tasks without directives or instruction. In addition to investigating treatment effects, the longterm maintenance of the task-change behavior was measured. During self-recording and picture-cue training, the subjects completed an increased proportion of independent task ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 9 publications
2
38
0
Order By: Relevance
“…These results replicate and extend those reported by previous investigators (e.g., Connis, 1979;Johnson & Cuvo, 1981;Martin et al, 1982;Sowers et al, 1980;Spellman et al, 1978;Thinesen & Bryan, 1981) Gold, 1972;Irvin & Bellamy, 1977). However, in addition to being effective in the acquisition phase of training, the efficacy of instructional procedures must also be evaluated with respect to subsequent or concurrent generalization and maintenance of performance.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These results replicate and extend those reported by previous investigators (e.g., Connis, 1979;Johnson & Cuvo, 1981;Martin et al, 1982;Sowers et al, 1980;Spellman et al, 1978;Thinesen & Bryan, 1981) Gold, 1972;Irvin & Bellamy, 1977). However, in addition to being effective in the acquisition phase of training, the efficacy of instructional procedures must also be evaluated with respect to subsequent or concurrent generalization and maintenance of performance.…”
Section: Resultssupporting
confidence: 92%
“…Requests for reprints should be sent to David P. Wacker, Division of De-velopmental Disabilities, The University of Iowa, Iowa City, Iowa 52242. Connis (1979) and Sowers et al (1980) used picture prompts to train mentally retarded clients to become more independent in vocational settings. Connis used picture sequences to train moderately mentally retarded clients to change work tasks independently.…”
Section: The University Of Iowamentioning
confidence: 99%
“…Eleven studies were identified that outlined strategies for teaching transition-related behavior (Bryan and Gast 2000;Carson et al 2008;Cihak 2011;Cihak et al 2008Cihak et al , 2010Connis 1979;MacDuff et al 1993;Martin et al 1987;Massey and Wheeler 2000;Mechling and Savidge 2010;Newman et al 1995;Palmen et al 2012;Sainato et al 1987;Spriggs et al 2007). For example, Cihak (2011) compared the effects of static picture cues to video modeling on the between-task transition behavior of four students with ASD in a selfcontained classroom using an alternating treatment design.…”
Section: Antecedent-based Strategies For Teaching Transition-related mentioning
confidence: 99%
“…Use of pictures provides a good form of assistance for people who have learning difficulties. Using pictorial cues, students with intellectual disabilities have been taught to prepare foods (Martin, Rusch, James, Decker, & Trytol, 1982), to learn child-care skills Feldman, 2004;Feldman, Ducharme, & Case, L. (1999), to function more independently in a job setting (Connis, 1979) or in leisure activities (Bambara & Ager, 1992), to initiate and maintain grooming behaviours (Thinesen & Bryan, 1981), to develop pedestrian navigations skills (Kelley, 2012) and withdraw money and purchase items using a debit card (Alberto, Cihak, & Gama, 2005). Pictorial cues have been found to be more effective than verbal cues in promoting functional activities among children with disabilities (Caffó, Albano, Damato, & Stella, 2013;West, 2008).…”
Section: Introductionmentioning
confidence: 99%